The Concept of Pious Children in the Movie "Surau dan Silek": A Living Hadith Study - Muhammad Fajri (Jurnal Living Hadis, 2020)
This article delves into the reception of prophetic hadith in the movie “Surau dan Silek”, bringing with itself an assumption that human activities result from the attempts to understand, either textually or contextually, to the Quran and hadith. Employing reception theory, this article finds that the reception of the hadith in the movie “Surau dan Silek” is mostly exegetical and functional. In some cases the text of the hadith appear as part of the dialogue. In some other cases, the audience will only see the figures’ understanding of certain hadith. In either way, the main theme of the hadith dealt with throughout the movie is ‘being a pious child’. The script introduces ‘pious children’ as one of the so-called ‘amal jāriyah (continuous, never ending rewards) and goes on with the quite detail narrative of the characters of the ‘pious children’. This in itself shows that there has been a transformation of religious ideas, from the silent, not moving text in arid manuscripts to the colorful, cheerful yet religious characters. It is the technological development that allows such visual transformation to go off. It thus provides the society with quite new alternative ways to access and further understand prophetic hadith.